PENERAPAN METODE GALLERY WALK TERHADAP PEMBENTUKAN SIKAP DAN KEAKTIFAN SANTRI PONDOK PESANTREN DARUSSALAM SITIUNG 1 KAB. DHARMASRAYA - Ronoili, Ronoili; Imamora, Marjoni; Lizelwati, Novia (Sainstek : Jurnal Sains dan Teknologi, 2019)
This study aims to see the effect of the gallery walk method application to the attitudes and activeness of the students. The research data was obtained through quasi-experimental research by using randomized subjects posttest only controlled group design. This research was conducted at VIII grade students of MTsS Darussalam Sitiung 1 Islamic Boarding School Dharmasraya Regency which consisted of 2 classes with a population of 50 students. Samples were selected by simple total sampling technique, where the experimental and the controlled class were selected by lotting method. Data collection was carried out using observation and data analysis techniques through statistical tests consisting of normality, homogeneity and hypothesis tests with a significance level of 5%. Data from the hypothesis using the t test shows that the tcounted for the formation of attitudes, and activeness is 3.21 and 2.16, respectively with v = 48. Based on these values it is known that tcounted> ttable for the attitudes and activeness of students, namely (3.21> 1.677), and ( 2.16> 1,677) at the 5% significance level. Thus the hypothesis Ho is rejected and H1 is accepted, where the formation of the attitudes and activeness of students using the gallery walk method is better than using conventional learning with a certainty of 95%.